Inner Ear Therapeutics: An Overview of Middle Ear Delivery - Patel, Jaimin; Szczupak, Mikhaylo; Rajguru, Suhrud; Balaban, Carey; Hoffer, Michael E. (Frontiers in Cellular Neuroscience, 2019)
There are a variety of methods to access the inner ear and many of these methods depend on utilizing the middle ear as a portal. In this approach the middle ear can be used as a passive receptacle, as part of an active drug delivery system, or simply as the most convenient way to access the inner ear directly in human subjects. The purpose of this volume is to examine some of the more cutting-edge approaches to treating the middle ear. Before considering these therapies, this manuscript provides an overview of some therapies that have been delivered through the middle ear both in the past and at the current time. This manuscript also serves as a review of many of the methods for accessing the inner ear that directly utilize or pass though the middle ear. This manuscript provides the reader a basis for understanding middle ear delivery, the basis of delivery of medicines via cochlear implants, and examines the novel approach of using hypothermia as a method of altering the responses of the inner ear to damage.